The effects of financial literacy, digital financial literacy, technological literacy, perceived risk, and trust in artificial intelligence on trust in financial technology - Winda Kartika; Farah Margaretha Leon (Journal of Management Small and Medium Enterprises (SMEs), 2026)
There is a growing need to comprehend what influences consumers' confidence in online banking and other digital financial services due to the exponential growth of financial technology (FinTech). This research delves into the ways in which digital financial literacy, technology literacy, perceived risk, trust in artificial intelligence, and financial literacy impact the confidence that people in Indonesia have in FinTech. To provide a more thorough explanation of trust creation, perceived risk was included in the study model. The data was analyzed using Structural Equation Modeling (SEM) with AMOS. A total of 236 employed postgraduate students from the Greater Jakarta region were surveyed using purposive sampling. Digital financial literacy does not substantially impact users' trust, but financial literacy has a substantial negative impact on FinTech trust, according to the empirical results. confidence in FinTech is favorably impacted by technical literacy and confidence in AI, but it is significantly negatively impacted by perceived risk. Among the factors that were taken into consideration, people' faith in FinTech is most strongly explained by their confidence in artificial intelligence. The results of this study add to our knowledge of how people trust digital financial services by demonstrating the importance of users' perceptions of AI-related trust and risk, and by indicating that, in the FinTech context of Indonesia, factors related to technology have a greater impact on users' trust than factors related to literacy. Keywords: Digital Financial Literacy; Financial Literacy; Perceived Risk; Trust; Technological Literacy; Artificial Intelligence; Financial Technology